Challenges of communication in Central America. The wall of the lynchings: the speech of the hearings before news about gangs on Facebook - Willian Carballo (Realidad, 2017)
Every time a news about gangs is reported in digital newspapers - whether these are the perpetrators or that one of their members has been killed - the media feedback platforms are filled with different reactions from the readers. The discourse of these news has already been well studied. However, there is no analysis of how audiences perceive such information and react to it. Taking into account that gap, this research took as a sample the comments of the readers posted on Facebook after the journalistic publication of two violent acts related to gang members. The speech reflects a contradiction among the readers: on the one hand, they repudiate the violence exerted by the gangs; and on the other, they justify it and even demand it and cause them rejoicing when the sufferer is a member of gangs. A narrative coherent with the journalistic stories, which have incited fear and encouraged the strong hand as a solution.  Realidad: Revista de Ciencias Sociales y Humanidades No. 149, 2017: 147-169